FORMAT AND CONTENT OF PRIMARY CURRICULUM IN THE UNITED KINGDOM OF GREAT BRITAIN AND NORTHERN IRELAND COMPARATIVE ANALYSES - Iryna Borysenko (Порівняльно-педагогічні студії, 2019)
Current reforms in education system in all European countries involve modernization of the education content in terms of implementation of new educational standards, programmes of study and textbooks, refining teaching approaches. It actualizes comparative studies in order to outline achievements of European education and to define opportunities to use them in an innovative and efficient way in Ukrainian education.